New pro-inflammatory cytokine IL-40 is produced by activated neutrophils and plays a role in the early stages of seropositive rheumatoid arthritis - Navrátilová, Adéla; Bečvář, Viktor; Hulejová, Hana; Tomčík, Michal; Štolová, Lucie; Mann, Heřman; Růžičková, Olga; Šléglová, Olga; Závada, Jakub; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav; et al. (RMD open, 2023)
OBJECTIVE: Interleukin (IL)-40 is a new cytokine related to immune system function and malignancies. Recently, an association of IL-40 with rheumatoid arthritis (RA) and externalisation of neutrophil extracellular traps (NETosis) was found. As neutrophils are implicated in RA development, we investigated IL-40 in early stages of RA (ERA). METHODS: IL-40 was determined in serum of treatment naïve patients with ERA at baseline (n=60) and 3 months after initiation of conventional therapy and in healthy controls (HC; n=60). Levels of IL-40, cytokines and NETosis markers were measured by ELISA. NETosis was visualised by immunofluorescence. In vitro experiments were performed on peripheral blood neutrophils from ERA patients (n=14). Cell-free DNA was analysed in serum and supernatants. RESULTS: Serum IL-40 was elevated in ERA compared with HC (p<0.0001) and normalised after 3 months of therapy (p<0.0001). Baseline serum IL-40 correlated with rheumatoid factor (IgM) (p<0.01), anti-cyclic citrullinated peptide (p<0.01) autoantibodies and NETosis markers (proteinase 3; neutrophil elastase (NE); myeloperoxidase) (p<0.0001). Levels of NE significantly decreased after therapy (p<0.01) and correlated with the decrease of serum IL-40 (p<0.05). In vitro, neutrophils enhanced IL-40 secretion following NETosis induction (p<0.001) or after exposure to IL-1β, IL-8 (p<0.05), tumour necrosis factor or lipopolysaccharide (p<0.01). Recombinant IL-40 up-regulated IL-1β, IL-6 and IL-8 (p<0.05 for all) in vitro. CONCLUSION: We showed that IL-40 is significantly up-regulated in seropositive ERA and decreases after conventional therapy. Moreover, neutrophils are an important source of IL-40 in RA, and its release is potentiated by cytokines and NETosis. Thus, IL-40 may play a role in ERA.
Keywords: cytokiny; interleukiny; revmatoidní artritida; Interleukins; Neutrophils; Humans; autoprotilátky; Cytokines; interleukin-8; Interleukin-8; Early Rheumatoid Arthritis; neutrofily; Autoantibodies; Arthritis, Rheumatoid; lidé